2012
DOI: 10.1115/1.4006587
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analysis of the Effect of Variable Blade Row Spacing in a Subsonic Axial Turbine

Abstract: Numerical and experimental investigations have been performed to determine the effect of a variation of the interblade row axial gap on turbine efficiency. The geometry used in this study is the 1.5-stage axial flow turbine rig of the Institute of Jet Propulsion and Turbomachinery at Rhejnisch Westfalische Technische Hochshule (RWTH) Aachen University. The influence of the blade row spacing on aerodynamics has been analyzed by conducting steady and unsteady Reynolds-averaged Navier-Stokes (RANS) simulations as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In this case, the impact is stronger at blade hub, while tip sections undergo a reduced effect. Walraevens et al and Restemeier et al [6,41] found the same effect in their works.…”
Section: Axial Gap Effect On Stage Performancesupporting
confidence: 54%
See 1 more Smart Citation
“…In this case, the impact is stronger at blade hub, while tip sections undergo a reduced effect. Walraevens et al and Restemeier et al [6,41] found the same effect in their works.…”
Section: Axial Gap Effect On Stage Performancesupporting
confidence: 54%
“…However, some of the physical mechanisms involved in the variation on axial gap are identified and can be useful for the designer to address the aerodynamic design of the stage. [5,41] in terms of absolute value. They found an efficiency variation of about 0.2-0.3%, even if in these works the position of maximum gain is located at higher axial gap.…”
Section: Discussionmentioning
confidence: 99%
“…Aerodynamic considerations set the spacing between HPT stator and rotor blade rows. 11,12 The inter-disc spacing is therefore a function of the disc widths which must be limited for both HPT discs to fit. A preliminary sizing of the HPT discs was carried out for both the GIRFC and GISFC concepts.…”
Section: Impact Of Core Configuration On Blade Heightmentioning
confidence: 99%
“…Restemeier et al also conducted similar research on the turbine test (RWTH) of Aachen University. It should also be noted that the smaller stage gap is more conducive to improving the efficiency of turbines with small aspect ratios [13]. Researchers still lack a mature theory of the influence of axial gap changes on turbine flow characteristics [14].…”
Section: Introductionmentioning
confidence: 99%